Fabrication and Characterization of Glucosamine Hydrochloride from Chitin of Horseshoe Crab Shell (Tachypleus gigas) - Nasution, Aurora Khairani; Agusnar, Harry; Alfian, Zul (Talenta Publisher, 2021)
Preparation of glucosamine hydrochloride from the chitin of horseshoe crab shells using the chemical hydrolysis method has been done using HCl concentration variation ratios of 7%, 9%, 11%,14 % with a ratio of 9:1 (v/w) for 4 hours at a temperature of 90ÂºC. Determination of glucosamine hydrochloride characteristics was characterized using Fourier transform-infra red (FT-IR) spectroscopy, in which the characteristics of glucosamine hydrochloride obtained in the OH group of glucosamine hydrochloride were 3446 cm-1 (s), 3448 cm-1 (s), 3450 cm-1 (s), 3448 cm-1 (s), respectively. For NH group of glucosamine hydrochloride were 1557 cm-1 (s), 1559 cm-1 (s), 1556 cm-1 (s), 1560 cm-1 (s), respectively. For CN group of glucosamine hydrochloride were 1379 cm-1 (m), 1379 cm-1 (m), 1379 cm-1 (m), 1379 cm-1 (m), respectively. While the glycoside bond of glucosamine hydrochloride 1073 cm-1 (w), 1074 cm-1 (w), 1074 cm-1 (w), 1074 cm-1 (w), respectively. Determination of the concentration of glucosamine hydrochloride with Ultraviolet Spectrophotometer analysis at a maximum wavelength of 197 nm with a standard solution of N-acetyl glucosamine in a solution of phosphate acid 0.005%, in which obtained the concentration of glucosamine hydrochloride 7% = 33.67 ppm, 9% = 36.35 ppm, 11% = 40.16 ppm, 14% = 43.97 ppm.